Neuropsychological Changes in Primary Hyperparathyroidism after Parathyroidectomy. Issue 9 (September 2016) - Liu, Jessica Y.; Saunders, Neil D.; Chen, Aaron; Weber, Collin J.; Sharma, Jyotirmay
Neuropsychiatric symptoms (NPSs) of sporadic primary hyperparathyroidism (PHPT) are often subtle and effects of parathyroidectomy (PTX) on symptoms remains poorly characterized. Our aim was to evaluate effects of PTX on NPS in patients with PHPT. A prospective questionnaire was distributed to all patients undergoing PTX and to a thyroidectomy (TX) control group. The questionnaire included the validated scales Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7) to assess for depression and anxiety respectively, as well as questions modified from Pasieka's Parathyroid Assessment of Symptoms (M-PAS). Point values were assigned to questionnaire answers to create a score, with a maximum of 63. Fifty-eight patients underwent PTX (58.6%) and 41 TX (41.4%). Mean preoperative scores were greater in PTX versus TX patients in total score, PHQ-9, GAD-7, and M-PAS (all P < 0.05). Post-PTX scores were lower than pre-PTX in total score, PHQ-9, GAD-7, and M-PAS (all P < 0.05), but not in pre- and post-TX. Post-PTX 69.0 and 82.8 per cent of patients showed no symptoms of depression and anxiety, respectively, compared with 37.9 and 56.9 per cent pre-PTX. A total of 16.2 and 10.3 per cent of patients had moderately severe to severe depression and anxiety, which fell to 0 per cent post-PTX. NPSs are more common in patients with PHPT when compared with TX. Patients undergoing PTX have improvements in NPS. NPS scoring should occur in all patients with PHPT and severity of NPS should be considered a relative indication for PTX.